Analisis Akurasi Model Altman Modifikasi (Z”-Score), Zmijewski, Ohlson, Springate dan Grover Untuk Memprediksi Financial Distress Klub Sepak Bola - Inayatul Lutfiyyah; Loggar Bhilawa (Jurnal Akuntansi, 2021)
This study aims to find an accurate financial difficulty prediction model in English Premier League football, and also to compare with previous research so as to obtain the results of a financial difficulty prediction model that can be used for all football clubs. The way to determine the sample to be examined is using purposive sampling technique with a population of 49 English premier league clubs from 1992-2018, so that the number of samples obtained is 37 samples and then grouped in the categories of financial distress and nonfinancial distress. The method for analyzing data uses the model's accuracy test by comparing the model's prediction results with financial distress and nonfinancial distress sample categories and considering the results of the type 1 and type 2 error levels of each model. Error level 1 results from the sum of prediction errors that are actually financial distress but the results of the prediction of the nonfinancial distress model and vice versa. The results show that the model that has the highest level of accuracy for predicting financial distress in English premier league soccer clubs is the Zmijewski model with an accuracy rate of 72%. Keywords: Financial Distress, Football Club, Accuracy Test, Error Rate